Identity Politics in the 2018 Regional Head Elections for the Governor and Deputy Governor of North Sumatra - Edy Syofian; Subhilhar Subhilhar; Heri Kusmanto; Muryanto Amin (Budapest International Research and Critics University, 2020)
The election of the Governor and Deputy Governor of North Sumatra Province in 2018 presents a unique practice of identity politics with the complexity of the political system and democratic practices. This research finds the practice of identity politics running in the 2018 Pilgubsu process, where each candidate uses closeness in ethnicity and religiosity in political practice; campaign until the selected work program.In accordance with the characteristics of the data, the research method used in this study is a qualitative approach with the main focus is to explain the factors that led to the emergence of religious identity politics in multicultural societies in North Sumatra through a democratic process. Data collection techniques used observation, literature review and in-depth interviews. The data obtained were analyzed and outlined in the form of field reports. The results of the study illustrate thatGovernor-elect Edy Rahmayadi explicitly and implicitly acknowledged the use of identity politics in the 2018 Pilgubsu contest; campaign slogans, campaign processes to success teams through various political media. The practice of identity politics in the 2018 Pilgubsu is inseparable from a series of national politics from the post-reform era to direct elections since the era of regional autonomy. The long political dialogue then resulted in political reconfiguration as a movement towards the development of positive political discourse and as part of further political education for the wider community. The reconstruction of the democratic process in the context of direct regional head elections is carried out to minimize the negative impact by political parties and the government on the direct regional head election process.